KASIH ALLAH AKAN DUNIA INI: PANGGILAN UMAT KRISTEN UNTUK MENGASIHI INDONESIA (GOD'S LOVE FOR THIS WORLD: CHRISTIANS CALL TO LOVE INDONESIA) - Yan Suhendra; Susanti Embong Bulan (Widya Agape School of Theology and Indonesia Christian Theologians Association, 2021)
Some church leaders say that Christians should hate and stay away from this world. This world will be destroyed. This has an impact on the indifference of Christians to the future of this world, including the future of the Indonesian state. Some Christians have the opinion that the most important thing is the new world (heaven). The text of John 3:16 gives us deep meaning in how we view the world (Indonesia). The research method used in this article is biblical ecegesis with a syntactic and semantic grammatical analysis approach. The result of this research is that God loves this world. By loving this world, every Christian is also called and involved to love, which is to care for this world, including the Indonesian nation. Sebagian pemimpin gereja mengatakan bahwa umat Kristen harus membenci dan menjauh dari dunia ini. Dunia ini akan hancur. Hal ini memiliki dampak pada ketidakpedulian umat Kristen terhadap masa depan dunia ini, termasuk masa depan negara Indonesia. Sebagian umat Kristen memiliki anggapan bahwa yang terpenting adalah dunia baru (sorga). Teks Yohanes 3:16 memberikan kita makna yang dalam bagaimana kita memandang dunia ini (Indonesia). Metode penelitian yang digunakan pada artikel ini adalah eksegesis biblis dengan pendekatan analisa gramatika sintaksis dan semantik. Hasil dari penelitian ini adalah bahwa Allah mengasihi dunia ini. Dengan mengasihi dunia ini, maka setiap umat Kristen juga dipanggil dan terlibat untuk mengasihi, yaitu memelihara dunia ini, termasuk bangsa Indonesia.